Toxic effects of per- and polyfluoroalkyl substances on sperm: Epidemiological and experimental evidence - Sun, Zhangbei; Wen, Yiqian; Wang, Binhui; Deng, Shiyi; Zhang, Fan; Fu, Zhendong; Yuan, Yangyang; Zhang, Dalei (Frontiers in Endocrinology, 2023)
As emerging organic contaminants, per- and polyfluoroalkyl substances (PFASs) have aroused worldwide concern due to their environmental persistence, ubiquitous presence bioaccumulation, and potential toxicity. It has been demonstrated that PFASs can accumulate in human body and cause multiple adverse health outcomes. Notably, PFASs have been detected in the semen of human, posing a potential hazard to male fecundity. This article reviews the evidence about the toxic effects of exposure to PFASs on male reproduction, focusing on the sperm quality. Epidemiological studies showed that PFASs, such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS), were adversely associated with the semen parameters in humans, including sperm count, morphology and motility. Experimental results also confirmed that PFAS exposure led to testicular and epididymal damage, therefore impairing spermatogenesis and sperm quality. The mechanisms of reproductive toxicity of PFASs may be involved in blood-testosterone barrier destruction, testicular apoptosis, testosterone synthesis disorder, and membrane lipid composition alteration, oxidative stress and Ca2+ influx in sperm. In conclusion, this review highlighted the potential threat of exposure to PFASs to human spermatozoa.